Horticulture on the farm - Havens, Alonzo Charles (My University, 1896)
Introduction: Attention to this work, doing much toward showing that the highest happiness of the farmer is not in the possession of more and more land, but in the better culture of the smaller amount. “The majority of the American farmers have no garden worthy to be called a family garden.” The little patch of ground set apart for that purpose is allowed to grow up to weeds, and become an eyesore to the whole family. The orchards of many farmers are in but little better condition, consequently the fruit is liable to be imperfect and uninviting. Even farmers who have good apple orchards neglect the raising of small fruits, for want of time and patience.
Citation: Havens, Alonzo Charles. Horticulture on the farm. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Happiness; Farmer; American farmers; Theses; Manuscripts (documents)